PENGARUH KUALITAS LAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN PT. RAHMAN WISATA MANDIRI JAKARTA - Annes Ayunda Putri; Iwan Kurniawan Subagja (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2017)
Nowadays, the increasing need for transportation services has become a basic and major requirement. One of the causes of the increasing need for transportation is the interest to carry out various activities quickly and appropriately. This condition can be seen from the government's support for equitable regional economic growth by opening all access using various transportation modes created. However, in utilizing all these facilities, the public or users of transportation services often have limitations in ordering for various things. Then arose several companies managing transportation services with various facilities either through the services of land transportation, sea transportation, and air transportation services. In an effort to serve the needs of these service users, companies use a variety of media and infrastructure that in turn aims to maximize service and win the competition. This study aims to analyze the effect of service quality and product quality on customer satisfaction PT. Rahman Wisata Mandiri Jakarta simultaneously or partially. The number of samples was 42 respondents. The sampling technique in this research is by using saturation sampling technique. The saturated sample is a sample determination technique when all members of the population are used as a sample. The results showed that there is both partial and simultaneous effect of service quality and product quality on customer satisfaction of PT. Rahman Wisata Mandiri Jakarta.